Updated management for patients with cardiovascular disease and diabetes. Issue 8 (August 2019) - Dugan, Joy; Butts, Amy; Collins, Billy St. John; Saini, Parmjeet S.; Bradley, Sarah
Abstract : ABSTRACT: Atherosclerotic cardiovascular disease (ASCVD) is the leading cause of morbidity and mortality for patients with diabetes. The latest guidelines from the American Diabetes Association include new information on hypertension, lipid management, heart failure, and coronary heart disease. This year, for the first time, the cardiovascular disease and risk management section was endorsed by the American College of Cardiology. Primary and secondary prevention of ASCVD is a critical element of the primary care visit for patients with diabetes. This article provides key highlights that are important for busy clinicians.